Toghu as Indigenous Knowledge and Cultural Enterprise: Material Traditions, Identity, and National Integration in Cameroon - Abianji-Menang, Ophilia A. (Advances in Social Sciences Research Journal, 2026)
This paper examines Toghu, a traditional hand-embroidered regalia from the Grassfields region of Cameroon, as both an expression of Indigenous Knowledge Systems (IKS) and a dynamic cultural enterprise that fosters national integration, cultural identity, and sustainable livelihoods. The colonial experience in Cameroon produced two dominant cultural identities—French and English—whose coexistence since the 1961 reunification remains challenged by the ongoing Anglophone crisis. Against this backdrop of division, Toghu has emerged as a unifying national symbol, bridging ethnic, linguistic, and regional divides while promoting shared cultural pride and social cohesion. Although Toghu has largely been studied as a cultural artifact and ceremonial attire, limited scholarship interrogates its triple function as a knowledge system, a women-led economic practice that sustains local artisans, particularly women and youth and economic practice capable of bridging historical, linguistic, and postcolonial divides in Cameroon. Addressing this gap, the study positions Toghu within broader debates on cultural assimilation and multicultural coexistence through the lenses of the Melting Pot and Salad Bowl theories. Employing qualitative cultural analysis, the study draws on artifact study, literature review, and ethnographic observation of Toghu production, circulation, and performance in ceremonial, festive, national, and diasporic contexts. Findings reveal that Toghu transcends its Grassfields origins to function as a site of intergenerational knowledge transmission, aesthetic continuity, socio-economic empowerment and has become a powerful symbol of national unity and cultural resilience.. Women emerge as central actors, exercising creative agency, artisanal expertise, and leadership in production and trade, ensuring both the craft’s sustainability and its contribution to household and community livelihoods. The study argues that Toghu simultaneously operates as cultural heritage, developmental strategy, and instrument of national integration. By preserving indigenous creativity, promoting inclusive identity formation, and empowering women artisans, it demonstrates the transformative potential of Indigenous Knowledge Systems to reconcile colonial legacies, reinforce collective belonging, and advance sustainable cultural enterprise. Ultimately, Toghu functions/emerges as both a material repository of memory and a contemporary instrument for creativity, socio-economic empowerment, and nation-building in Cameroon.